Edmund Burke i rewolucyjne korzenie totalitaryzmu - Tulejski, Tomasz; Bosiacki, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article discusses the roots of revolutionary totalitarianism in the thought of Edmund Burke, who is considered to be the founder of Anglo-Saxon conservatism. The author of Reflections on the Revolution in France insightfully outlined the totalitarian implications of the French Revolution at its initial stage. According to the authors, Burke accurately diagnosed the most important elements of the future totalitarian state, affecting not only institutions, but also the overall social relations and the interplay between the authority and the individual. His reflections on revolutionary ideas and revolutionary practice make him a prophet of future totalitarian regimes, which operated according to the paradigm he diagnosed. Although Burke’s theses seem commonly known, a closer analysis shows not only the depth of the inquiry into the French revolution, but also the universality of the argument applicable to other similar social upheavals, a topic the authors of the text would like to present together in a separate form.
Keywords: French Revolution 1789; enlightenment in France; egalitarianism; populism; totalitarianism; revolutionism; Edmund Burke (1729–1797); ancien régime; Roman Catholic Church